2020
DOI: 10.1165/rcmb.2020-0241oc
|View full text |Cite
|
Sign up to set email alerts
|

Immune Modulation to Improve Survival of Viral Pneumonia in Mice

Abstract: Viral pneumonias remain global health threats, as exemplified in the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic, requiring novel treatment strategies both early and late in the disease process. We have reported that mice treated before or soon after infection with a combination of inhaled Toll-like receptor (TLR) 2/6 and 9 agonists (Pam2-ODN) are broadly protected against microbial pathogens including respiratory viruses, but the mechanisms remain incompletely understood. The objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…11 More recently, we showed that Pam2ODN can attenuate chronic asthma-like lung disease in mice infected with Sendai virus (SeV). 12 We reasoned that Pam2ODN would exert a protective effect against the chronic disease by reducing the viral burden in the acute infection, but we observed some efficacy when Pam2ODN treatment was given at remote time points when the virus burden was not reduced in the acute infection. This partial discordance between the reduction in viral burden and chronic disease severity led us to hypothesize that Pam2ODN also modulated the type 2 immune response that drives the chronic disease.…”
Section: Manuscript Text Introductionmentioning
confidence: 88%
“…11 More recently, we showed that Pam2ODN can attenuate chronic asthma-like lung disease in mice infected with Sendai virus (SeV). 12 We reasoned that Pam2ODN would exert a protective effect against the chronic disease by reducing the viral burden in the acute infection, but we observed some efficacy when Pam2ODN treatment was given at remote time points when the virus burden was not reduced in the acute infection. This partial discordance between the reduction in viral burden and chronic disease severity led us to hypothesize that Pam2ODN also modulated the type 2 immune response that drives the chronic disease.…”
Section: Manuscript Text Introductionmentioning
confidence: 88%
“…TLR binding and signaling has been reviewed in detail recently [ 28 ], thus the focus here will be on recent advances during lung infection. Administration of a cocktail of TLR agonists (Pam2-ODN, TLR2/6 and 9 agonists) during Sendai paramyxovirus infection leads to alleviation of lung epithelial damage early in infection, reduced viral burden and decreased mouse mortality [ 30 ]. In an observational study, elderly patients with severe pneumonia exhibited lower levels of monocyte TLR2 and TLR4 expression, correlating with diminished serum concentrations of interleukin-1 (IL-1), interleukin-6 (IL-6), and TNF-α [ 31 ].…”
Section: Pattern Recognition Receptors and Signaling Pathwaysmentioning
confidence: 99%
“…An important question that needs to be addressed is why the lungs of mice were harvested six days after exposure to Pam2-ODN, a toll-like receptor agonist. Inhalation of Pam2-ODN has been shown to protect mice infected with virus or bacteria few hours after exposure to the toll-like receptor agonist (2)(3)(4). Therefore, it is conceivable that earlier evaluation of lung microbiota would have provided different results.…”
Section: To the Editormentioning
confidence: 99%